Analysis of Energy Dissipation and Sealing Performance of the Premium Connection in Modal Vibrations - Yang Yu; Yang Liu; Yinping Cao; Qingying Yuan; Jiarui Tang; Yihua Dou (Applied Sciences)
Traditional static analysis cannot effectively explain the issue of the sealing performance of the premium connection being decreased due to the vibration of the tubing, leading to the failure of the connection sealing. In this paper, based on the energy dissipation theory and considering the influence of the micro contact slip of the sealing surface under the vibration of the tubing, a finite element model of the premium connection is established. The natural frequency and vibration mode are obtained through modal analysis experiments, and the accuracy of the finite element model is verified. The results show that the first five natural frequencies are mainly concentrated in the axial direction of the tubing, with the amplitude of the radial vibration mode being small. The vibration mode results are applied to the model as boundary conditions. It is found that an increase in the axial displacement amplitude leads to an increase in the energy dissipation of the sealing surface of the premium connection, which reduces the normal contact pressure and the effective length of the sealing surface, ultimately leading to a decrease in the sealing performance.